Gut Resistome of Preschool Children After Prolonged Mass Azithromycin Distribution: A Cluster-randomized Trial. (26th May 2021) - Arzika, Ahmed M; Maliki, Ramatou; Abdou, Amza; Mankara, Alio K; Harouna, Abdoul N; Cook, Catherine; Hinterwirth, Armin; Worden, Lee; Zhong, Lina; Chen, Cindi; Ruder, Kevin; Zhou, Zhaoxia; et al.
Abstract: We evaluated the gut resistome of children from communities treated with 10 twice-yearly azithromycin distributions. Although the macrolide resistance remained higher in the azithromycin arm, the selection of non-macrolide resistance observed at earlier time points did not persist. Longitudinal resistance monitoring should be a critical component of mass distribution programs. Clinical trials registration: NCT02047981